Pelatihan Google Workspace, Pengelolaan Web dan Informasi Berbasis Cloud Organisasi Lingkungan Warga Katolik di Poris Residence – Kota Tangerang - Henri Septanto; Bias Yulisa Geni; Wenny Desty Febrian (Jurnal Karya untuk Masyarakat (JKuM), 2025)
Web management and cloud based information management for an organization, including small organizations, is very necessary so that the organization's website, data and information can be well maintained and can be displayed and used at any time for various organizational needs. In the current digital era, conveying information in the form of announcements via messaging applications such as WhatsApp is no longer effective because often, because of the large amount of information, messages become piled up and difficult to find. Conveying information quickly and efficiently is what is an obstacle in this organization, for this reason the PKM team of lecturers and students was moved to provide training on cloud-based web and information management to administrators of the Poris Residence Catholic community organization, Tangerang City as a solution to overcome this obstacle. After attending this training, organizational administrators have better web and information management skills, they are even able to manage web-based information media that can be accessed by all members of the organization. The results of the training can be felt by the entire organization because important information can now be conveyed more quickly, clearly and efficiently.